(untitled) (Discourse of Law and Administration, 2024)
In order to treat a patient who came to Poland in 2012, under an out-of-court compensation system, for a medical event. It was based on the effect of provincial inspectors in deciding on a disease event. Their extensive structure and inefficiency in providing new legal solutions. Other sources show that 2023 are available for determining health effects from the Patient Ombudsman, as well as side effects from the Medical Event Compensation Fund. The aim of the work is to analyze, summarize and evaluate the law: legal basis, amount and duration of the proceedings. The analysis showed that the problem was definition. Moreover, it still limits the possibility of investigation only in the hospital. There are also reservations about the introduction of an amount limit as a solution similar to the one already introduced and for use from the Medical Event Compensation Fund. Instead, the introduction of the no-fault principle in the new compensation system should be taken 262 Joanna Zdanowska into account, as well as clarifying the list of persons who can be entered into the Ombudsman with consequences for compensation of damages in the event of the patient’s death in the place of heirs.